Efectos sociales de la globalización en el sector porcícola colombiano bajo la perspectiva de la gestión integral (2010)
This article aims to present some reflections on the thinking of Amartya Sen (Nobel laureate in economics 1998), set out in his article “Judgments on globalization”, and the relation of these reflections with the pork industry in Colombia. The work is divided into two parts, the first is about whether or not the pork industry has the possibility of entering international markets, and the second about the social effects in the pork industry caused by globalization. Each of the parties’ concluding remarks intend to unsettle the reader about how globalization is assumed in the pork industry's intention to reach a competitive international market. It also presents some environmental, social and economic globalization effects brought to this sector. To accomplish this work it was important to contact the Colombian Association of Pork-FNP (Asoporcicultores - FNP) and the National Council for Economic and Social-CONPES for the pork industry.